Mood Disorder Symptoms and Quality of Life in Women Attending a Specialized Vulvar Clinic in Southern Sweden - Magnúsdóttir Halfin, Helga; Löfroth, Anna; Siemund, Ingrid; Dalgard, Florence (Journal of Lower Genital Tract Disease, 2026)
Objectives: – To evaluate the prevalence of mood disorder symptoms and measure the quality of life in women with vulvar dermatoses attending a specialized vulvar clinic in southern Sweden. Materials and Methods: – A questionnaire-based study among consecutive women attending the vulvar unit at the Department of Dermatology and Venereology at Skåne University Hospital. Sociodemographic factors were collected; depression and anxiety were assessed with the Hospital Anxiety and Depression Scale (HADS) and health-related quality of life with the EQ-5D VAS. Results: – In all, 217 of 242 women participated (response rate 90%). Data was collected from March 2020 to January 2023. The largest diagnostic group was lichen sclerosus (62%), followed by lichen planus (9.2%) and pain disorders (5.5%). Symptoms of depression and anxiety were highest among women with pain disorders (n=12, anxiety symptoms 58.3%, depression symptoms 20%), followed by Candida vulvovaginitis (n=7, anxiety symptoms 57.2%, depression symptoms 0.0%) and pruritus vulvae (n=7, anxiety symptoms 42.9% and depression symptoms14.3%). Differences between these groups were not significant. The mean EQ-5D VAS score was 69.7±19.7. Conclusions: – Women with pain disorders, Candida vulvovaginitis, and pruritus vulvae showed the highest levels of mood symptoms. These findings support the importance of assessing mood symptoms and quality of life in the management of women with vulvar disease.
Keywords: anxiety; depression; quality of life; vulvar clinic; vulvar dermatoses